2019
DOI: 10.1111/jfpp.14245
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different cold storage times on quality of “Cuiguan” pear fruits during shelf life

Abstract: This study investigates the effects of different cold storage times (30 days—CS‐30d, 40 days—CS‐40d, and 50 days—CS‐50d) on quality of “Cuiguan” pear fruits during shelf life. The data showed that, compared with 0 days of cold storage, the weight loss and rot rate of the fruit on the shelf increased, the hardness and nutritional quality of the fruit decreased rapidly, and the deterioration rate of the fruit was aggravated. By comparing the quality changes of three storage periods fruits during the shelf life a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…PC2 explained 8.5% of the total variance of the original variables and was determined by the weight loss and color parameters, indicating a strong relationship between color variation and fruit weight loss. The relationship between these indicators was also observed in the PCA analysis of kiwi [43] and pear [44]. In the PC1 direction, there was a good distinction between the different storage times for each group (Figure 5A).…”
Section: Correlation and Principal Component Analysis Of Fruit Qualit...mentioning
confidence: 52%
“…PC2 explained 8.5% of the total variance of the original variables and was determined by the weight loss and color parameters, indicating a strong relationship between color variation and fruit weight loss. The relationship between these indicators was also observed in the PCA analysis of kiwi [43] and pear [44]. In the PC1 direction, there was a good distinction between the different storage times for each group (Figure 5A).…”
Section: Correlation and Principal Component Analysis Of Fruit Qualit...mentioning
confidence: 52%
“…On the other hand, the AA content in the banana fruits continuously decreased in all the sample variants during the storage (Figure 4B). Generally, a decline in the AA level in fruit peel samples could be the result of temperature-dependent degradation [68] and oxidative stress [69] under prolonged exposure to cold storage, which accelerates the degradation, such as peel necrosis [70]. Chen et al [32] observed similar results when banana fruit stored under prolonged storage exhibited a decline.…”
Section: Changes In Gsh Aa Tpc and Tcc Levelsmentioning
confidence: 93%
“…The ‘Cuiguan pear’ ( Pyrus pyrifolia Nakai.) is a famous pear cultivar in China and is widely cultivated in Southern China [ 4 ].…”
Section: Introductionmentioning
confidence: 99%